Mixed convection stagnation point flow of a hybrid nanofluid past a permeable flat plate with radiation effect - Salleh, Siti Nur Alwani; Bachok, Norfifah; Pop, Ioan (MDPI, 2021)
This article focuses on the stagnation point flow of hybrid nanofluid towards a flat plate. The cases when the buoyancy forces and the flow are in the opposite direction and the same direction are discussed. The effect of radiation and suction is also taken into account. The similarity transformations are used to convert the partial differential equations into nonlinear ordinary differential equations. These equations are computed numerically via the bvp4c function in MATLAB software. A comparison with the previously published articles is carried out, where an outstanding agreement is observed. The dual solutions exist in the case of opposing flow (λ<0) and the suction parameter S>0.6688 . Meanwhile, only unique solutions exist in the case of assisting flow (λ>0) . The existence of dual solutions leads to stability analysis. From the analysis, the first solution is confirmed as a stable solution. Furthermore, the heat transmission rate increases, while the skin friction coefficient decreases as the radiation rate increases. An increase in the radiation rate from 0 (no radiation) to 1.0 increases the heat transmission rate by 5.01% for water, 4.96% for nanofluid, and 4.80% for hybrid nanofluid. Finally, it is worth mentioning that the present study yields new and original results. This study has also not been done by other researchers, indicating its novelty.